O olhar dos alunos e dos professores sobre a informática no curso de licenciatura em matemática na UFPA - MACHADO, João Carlos Ribeiro (Universidade Federal do Pará, 2011)
This work aims to investigate the knowledge shown by the students of the course of Mathematics at Universidade Federal do Pará (UFPA), concerning the use of the computer science in its Education formation. To achieve that objective we used a methodology based on qualitative research, referring to the case study. We made a brief historical study on the educational computer science in Brazil; we highlighted the progresses and researches in the area and we mentioned the best ways to use them in education; we centered our investigations on the aspects related to the Mathematical Education of some educational software and the experiences with the use of computers; and, soon after, we got to our investigation, based on the writings of the students and Professors of the graduation course of Mathematics of UFPA. The information was obtained by means of questionnaires applied to the students during the second term of 2004 and to the Professors in the first term of 2005. We could observe through the analyses that students and Professors consider the insert of the computer science to the curriculum of graduation in Mathematics extremely important they highlight that this teaching doesn't still happen and if so it must be an effective part of the process of the Math teachers formation, because it can contribute to the improvement of the process of teaching/learning and it is a too much important tool for the education.